The impact of religious tourism on the economy and tourism industry - Budovich, Lidia Sergeevna (HTS teologiese studies, 2023)
Today, tourism, with its distinct and unique features, has become one of the largest and most profitable industries in the world economy and has provided a platform for changes in geographical spaces. This study was conducted with the aim of investigating the effects of religious tourism on the economic development of traditional settlements. The research method is descriptive and analytical. The independent variable is ‘religious tourism’, which is quantified by 10 components, and the dependent variables are ‘income’ and ‘employment’ in tourist areas, which are studied with 10 components in Russia, respectively. Data analysis was carried out in SPSS software, then a Pearson’s correlation test and simple linear regression were used. Moreover, Geographic Information System (GIS) software was used to show the traditional spatial weighting of the study. The regression results show that religious tourism has been effective by 0.77 on income, 0.66 on employment, and 0.72 on the economy of traditional settlements. In fact, the development of religious tourism in areas with religious and traditional rituals has had a positive effect on creating employment, increasing income and economic prosperity. In general, religious tourism, with its structural and functional features, is considered an important factor in revitalising the economy of regions with this privilege.Contribution: This article has proven the strong role of religious tourism on the economy and tourism industry in Russia with a quantitative analysis, which deserves the attention of cultural and tourism policymakers. In addition, the results of this research can be considered by other countries with different religions.